2013 IEEE Frontiers in Education Conference (FIE) 2013
DOI: 10.1109/fie.2013.6685044
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of single and mixed gender engineering enrichment programs for elementary students

Abstract: The Center for Pre-College Programs at New Jersey Institute of Technology sponsors a series of summer enrichment programs designed to increase academically talented students' interest in the fields of science, technology, engineering and mathematics (STEM). Programs such as these can be instrumental in informing young students about careers in engineering and technology and helping ensure they receive the academic background required to prepare for these careers in college. One of the programs has been designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 19 publications
2
8
0
6
Order By: Relevance
“…Consistent with findings in previous research, it appears that while attitudinal measures such as the MATES are useful in evaluating the effectiveness of most engineering curriculum materials 66 or STEM programs 67 they are not necessarily the most effective measures of change that results from programs designed for high achieving students [57][58][59][60] .…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Consistent with findings in previous research, it appears that while attitudinal measures such as the MATES are useful in evaluating the effectiveness of most engineering curriculum materials 66 or STEM programs 67 they are not necessarily the most effective measures of change that results from programs designed for high achieving students [57][58][59][60] .…”
Section: Discussionsupporting
confidence: 62%
“…Few meaningful differences were found between the males and females within the programs in terms of increased content knowledge or attitudes toward engineering although, consistent with conclusion drawn from reviews of recent research, marked differences were found among the three different gender grouped programs in terms of classroom climate and student interactions in the classroom [60][61] . And while no differences were found for male students, comparisons between the female students in the female-only programs and the mixed gender program did however find some potentially meaning differences in selfefficacy and perceptions of engineers related to issues of gender identity 61 .…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Female students have also shown more self-efficacy and confidence in terms of learning methods than male students, regardless of their lower self-efficacy in academic achievement [6] [8] . On the influence factors of students' self-efficacy, Hirsch (2013) concluded that students' interest in engineering, their learning experience and the interactive environment in classroom played significant roles [18] .…”
Section: Literature Reviewmentioning
confidence: 99%